Profile of Medico-legal Cases and Body Injuries in a Tertiary Hospital in Padang, Indonesia 2010-2020 - Noverika Windasari; Citra Manela; Taufik Hidayat; Rika Susanti (Faculty of Medicine, Universitas Padjadjaran, 2022)
Forensic medicine is a branch of medicine that examines victims for the benefit of justice. Doctors play an important role in documenting injuries or abnormalities on the victim's body in the patient's medical record. This study aimed to determine the characteristics of cases and injuries of patients at M Djamil General Hospital during the period of 2010–2020. This was a descriptive retrospective study on secondary data from the medical records of patients who were examined and consulted to the Forensic Department of Dr. M. Djamil General Hospital, Padang during 2010–2020. During this period, 11.729 patients (victims) were examined by and consulted to the Department. Most of the victims were male (70.6%) aged 10–19 years old (29.2%). Most of the victims were involved in a traffic accident, followed by persecution. Victims of traffic accident dominated the forensic pathology cases after sudden death. Abrasions and open wound injury were the most frequent types of injury, with head and neck as the body parts mostly affected. In terms of the type of wound, most victims experienced injuries caused by blunt force (87%). This study concluded that the forensic cases managed at the Dr. M. Djamil General Hospital vary with blunt forces by a traffic accident as the most frequent cause of injuries while the head and neck become the body parts that are most susceptible to injury, both for survivors and those who died.